Competition and Retail Gasoline Prices - Livingston, S. Morris; Levitt, Theodore (The Review of Economics and Statistics, 1959)
IN recent years there have been numerous investigations of the nature and effects of competition in gasoline retailing. Implicit in much of the discussion is the assumption that retail prices for the major brands are usually identical. This article tests this assumption. It also analyzes why prices in a community are as uniform as they are, and why there are such differences as do exist. It sheds light on how competition works in this important market, and on the role of price in a successful merchandising program. The conclusions are applicable in varying degree to other industries. Detailed studies were made of six metropolitan areas in the Midwest, with populations ranging from iIO,OOO to over five million, and with a wide range of conditions that might influence prices. On a particular day a nationally known research company read the prices off the pumps of each gasoline outlet in five of the cities. In the sixth the data were collected by a refiner-marketer during a particular week. In four cities it was possible to get rather complete information about each gasoline outlet.' Information was also compiled on other factors which might influence the price pattern, such as neighborhood characteristics and traffic densities.